RELATIONSHIP MARKETING BASED ON LINKS BETWEEN AGRIBUSINESS ACTORS AND EDUCATION (CASE STUDY AT PT. TANIKOTA AGRICULTURAL EDULESTARI) - Shelsiya Nikela; Agriani Hermita Sadeli; Mahra Arari Heryanto; Sulistyodewi Nur Wiyono (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The competition between business actors in the agricultural sector with almost the same form of business triggers competition between business actors. Companies compete with each other through their strategies in order to maintain the existence of their business and consumers, such as using relationship marketing strategy. This study aimed to understand the pattern of relationship marketing and value exchange at PT. Edusustainable Agricultural Tanikota in Dago, Bandung City. This study adopted a qualitative method with a case study design. The model used to identify stakeholder relationships was the six market models and the exchange of values between actors uses holo mapping. The results of the study indicated that PT. Tanikota Agriculture Edulestari already had five market models, namely the customer market, internal market, referral market, influence market, and recruitment market and do not yet have the potential stakeholders of supplier/alliance market. The exchange of value that occurs in this relationship is the exchange of products and services that generate income. Exchange of value in knowledge that were analyzed were in the form of cultivation insight, agro-education development, marketing and technology. The exchange of value on intangible benefits includes a sense of trust and commitment. Exchange of value in knowledge that were analyzed were in the form of cultivation insight, agro-education development, marketing and technology.